Identification of a PD-L1+Tim-1+ iNKT subset that protects against fine particulate matter–induced airway inflammation - Christina Li-Ping Thio; Alan Chuan-Ying Lai; Jo-Chiao Wang; Po-Yu Chi; Ya-Lin Chang; Yu-Tse Ting; Shih-Yu Chen; Ya-Jen Chang (JCI Insight, 2022)
Although air pollutants such as fine particulate matter (PM2.5) are associated with acute and chronic lung inflammation, the etiology of PM2.5-induced airway inflammation remains poorly understood. Here we report that PM2.5 triggered airway hyperreactivity (AHR) and neutrophilic inflammation with concomitant increases in Th1 and Th17 responses and epithelial cell apoptosis. We found that γδ T cells promoted neutrophilic inflammation and AHR through IL-17A. Unexpectedly, we found that invariant natural killer T (iNKT) cells played a protective role in PM2.5-induced pulmonary inflammation. Specifically, PM2.5 activated a suppressive CD4– iNKT cell subset that coexpressed Tim-1 and programmed cell death ligand 1 (PD-L1). Activation of this suppressive subset was mediated by Tim-1 recognition of phosphatidylserine on apoptotic cells. The suppressive iNKT subset inhibited γδ T cell expansion and intrinsic IL-17A production, and the inhibitory effects of iNKT cells on the cytokine-producing capacity of γδ T cells were mediated in part by PD-1/PD-L1 signaling. Taken together, our findings underscore a pathogenic role for IL-17A–producing γδ T cells in PM2.5-elicited inflammation and identify PD-L1+Tim-1+CD4– iNKT cells as a protective subset that prevents PM2.5-induced AHR and neutrophilia by inhibiting γδ T cell function.